Using social media As promotional method of Soccer88 clothing - , M FATAH YUSIAWAN, Supriyono S. S., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This graduating paper aims to discuss the short profile of Soccer88 cloth. Then, it explains the promotion using social media and its effectiveness based on their customersâ opinion. For collecting data of this research, the writer uses two methods: library research and field study. In library research, the writer reads several books. For field study, the writer interviews the owner of Soccer88 cloth. Besides, the writer also asks the customers to fill out the questionnaires. From the questionnairesâ result, the writer knows and analyzes the customersâ opinion about the effectiveness of promotion using social media. Overall, Soccer88 cloth is one of apparel business which has three social media for promotion, such as Facebook, Twitter and KASKUS. Most customers chose Facebook as the media when they want to get more information about the product of Soccer88 cloth. The customer chose direct communication via phone or Blackberry Messenger for ordering the product.